Foundations of economics - Begg, David; Fischer, Stanley; Dornbusch, Rudiger 1942-2002 (London : McGraw-Hill Education, 2003)
This new edition provides clear exposition and analysis of the principle of economics, focusing on the core theories and applications of the subject.
Includes index.
Keywords: Economics